2020
DOI: 10.1007/s12035-020-02018-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Altered miRNA Expression in a Piglet Model of Hypoxic Ischemic Brain Injury

Abstract: Hypoxic ischemic encephalopathy (HIE) is the most frequent cause of acquired infant brain injury. Early, clinically relevant biomarkers are required to allow timely application of therapeutic interventions. We previously reported early alterations in several microRNAs (miRNA) in umbilical cord blood at birth in infants with HIE. However, the exact timing of these alterations is unknown. Here, we report serial changes in six circulating, cross-species/bridging biomarkers in a clinically relevant porcine model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 138 publications
0
17
1
Order By: Relevance
“…miR-140-5p and miR-181a-5p, the miRNAs modulated in an enriched context, are miRNAs expressed both in glia and neurons. Although previous work has implicated them in similar pathological processes such as brain ischemia ( Casey et al., 2020 ; Moon et al., 2013 ; Han et al., 2018 ) and Alzheimer disease ( Akhter et al., 2018 ; Ansari et al., 2019 ; Rodriguez-Ortiz et al., 2020 ), their physiological functions remain poorly explored. Increasing evidence suggest that both miR-140-5p ( Ambrozkiewicz et al., 2018 ) and miR-181a-5p ( Chandrasekar and Dreyer, 2009 ; Rodriguez-Ortiz et al., 2020 ; Saba et al., 2012 ) play important roles in neurons and are required for proper cognition ( Gullett et al., 2020 ; Xu et al., 2018 ; Zhang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-140-5p and miR-181a-5p, the miRNAs modulated in an enriched context, are miRNAs expressed both in glia and neurons. Although previous work has implicated them in similar pathological processes such as brain ischemia ( Casey et al., 2020 ; Moon et al., 2013 ; Han et al., 2018 ) and Alzheimer disease ( Akhter et al., 2018 ; Ansari et al., 2019 ; Rodriguez-Ortiz et al., 2020 ), their physiological functions remain poorly explored. Increasing evidence suggest that both miR-140-5p ( Ambrozkiewicz et al., 2018 ) and miR-181a-5p ( Chandrasekar and Dreyer, 2009 ; Rodriguez-Ortiz et al., 2020 ; Saba et al., 2012 ) play important roles in neurons and are required for proper cognition ( Gullett et al., 2020 ; Xu et al., 2018 ; Zhang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One significant hurdle to designing miRNA-based therapies for neonatal HIBI is a lack of data describing the endogenous miRNA expression after neonatal HIBI. To date, there have been two studies that have profiled the serum miRNA changes in human newborns with HIE using high-throughput analyses using the same cohort but two different miRNA detection techniques ( Looney et al, 2015 ; Casey et al, 2020 ). Between the two studies, the investigators identified at least 107 miRNAs that were significantly up- or downregulated in newborns diagnosed with HIE.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that the miRNA profile would differ between the cortex and striatum/thalamus and that the cerebellar miRNA expression would be distinct from both of the other regions given its relative protection from ischemic injury in this model. As described above, all of the human studies were obtained immediately after delivery (i.e., cord blood) ( Looney et al, 2015 ; Casey et al, 2020 ), but previous studies in the piglet model of neonatal HIBI have demonstrated that many miRNAs do not reach peak dysregulation until around 1 h after injury ( Garberg et al, 2017 ; Casey et al, 2020 ). As such, to allow for comparison with the previous clinical studies (of cord blood at 0 min after injury) but also ensure time for miRNA dysregulation to occur (peak at 60 min after injury), the region-specific miRNA levels assessed in this study were all obtained at 30 min after injury, consistent with the timing used in other similar studies ( Yuan et al, 2010 ; Garberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have pointed out that miR-148a-3p was frequently closely associated with mental abnormality class diseases, such as susceptibility for panic disorder [9]. In hypoxic-ischemic encephalopathy, it was found that miR-148a-3p could be used as a potential biomarker to indicate the injury [10]. Lithium is one of the most widely certified anticonvulsants and mood stabilizers and exhibits significant neuroprotective effects in the treatment of epilepsy, and the neuroprotective effects of lithium have been reported to be achieved through regulating miR-148a-3p in Parkinson's disease [11].…”
Section: Introductionmentioning
confidence: 99%